Correction: Li et al. Nodal Facilitates Differentiation of Fibroblasts to Cancer-Associated Fibroblasts that Support Tumor Growth in Melanoma and Colorectal Cancer. Cells 2019, 8, 538 - Ziqian Li; Junjie Zhang; Jiawang Zhou; Linlin Lu; Hongsheng Wang; Ge Zhang; Guohui Wan; Shaohui Cai; Jun Du (Cells)
In the original publication, there was a mistake in Figure 1B as published [...]